Les sociétés locales rurales et le développement des gîtes dans la mégalopole de Shanghai - Emmanuel Véron (EchoGéo)
This article examines the forms of rural governance in the Yangtze River Delta megalopolis with regard to rural tourism. We study the role of communities and their integration into a new economic activity trough tourism services. These activities have led rural communities to reorganize their work, enrich their homes and morphologically transform villages. The study of two villages within the Yangtze delta illustrates local development through tourism and the evolution of rural people who have become tourist service providers.